Tailoring grain morphology in Ti-6Al-3Mo through heterogeneous nucleation in directed energy deposition. (20th October 2021) - Zhang, Fengying; Gao, Panpan; Tan, Hua; Li, Yao; Chen, Yongnan; Mei, Min; Clare, Adam T.; Zhang, Lai-Chang
Graphical abstract: Highlights: Almost fully-fine equiaxed grains are obtained in DED Ti-6Al-3Mo by satelliting. The <100> fiber texture of DED titanium alloy along deposition direction is reduced. The heterogeneous nucleation mechanism in DED Ti-6Al-3Mo by satelliting is revealed. The selection of α-variants is gradually reduced with the refinement of β-grains. Ti-6Al-3Mo with equiaxed grains shows a good combination of strength and elongation. Abstract: A common challenge in direct energy deposition (DED) is eliminating the anisotropy in mechanical performance associated with microstructure and the formation of coarse columnar grains. In this work, a heterogeneous nucleation mechanism was introduced into the melt pool, and, from this mechanism, an almost fully equiaxed grain morphology was obtained in the DED of Ti-6Al-3Mo. Three types of grain morphologies in DED Ti-6Al-3Mo, including full columnar grains, near-equiaxed grains and almost fully equiaxed grains were obtained from premixed and satellite powder blends from Ti, 6 wt.% Al and 3 wt.% Mo, respectively. Combined with the analysis of the interactions between powder particles and the melt pool in DED, the formation mechanism of the equiaxed grains caused by the incomplete melting of high melting point Mo particles was revealed. As the prior-β grains transformed from coarse columnar grains to fine-equiaxed grains, the strong <100> fiber texture along the deposition direction was weakened, while the size of the α-laths in the prior-β grains slightly decreased, and the selection of α-variants was weakened. Due to the transformation of the prior-β grains from coarse columnar grains to fine-equiaxed grains, the tensile strength of the deposited samples increased from 982 MPa to 1082 MPa, while the yield strength increased from 840 MPa to 922 MPa, and the elongation of the as-deposited alloy also increased from 9.0 % to 9.8 %, which confirmed that the presence of fine-equiaxed grains is beneficial to the strength and plasticity of the DED alloy. This work further demonstrates the role that satelliting powders can play in terms of enhancing the columnar to equiaxed transition (CET) behavior associated with DED.